Disease Severity and Clinical Outcome of Coronavirus Vaccinated Patients Following Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection - Sarkar, Nirmal Kanti; Roy, Moumita; Feroz, Salahuddin; Rahman, Md Ashadur (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background and aims: The severity of illness and mortality in coronavirus disease (COVID-19) may be curtailed byvaccination. We assessed the disease severity and clinical outcome in coronavirus vaccinated patients following SARSCoV-2 infection. Methods: We conducted an observational study among theSARS-CoV-2 infected patients who received one or two doses of a single generic type of coronavirus vaccine (ChAdOx1nCoV-19, Covishield®, Serum Institute of India) at the outset of vaccine rollout program in Bangladesh. Eligible patients treated at home, outpatient basis, or hospitalized between April 10, 2021, and June 18, 2021, were included. Demographic characteristics, clinical presentation, comorbidities, radiological features, disease severity, treatment protocol, and outcomes were evaluated. The primary end point was disease severity (mild, moderate, severe, and critical).The secondary endpoint was clinical outcome (complete recovery or death) at day 28. Results: The cohort included total 61 patients. Age ranged between 23–82 year; majority were male (62.3%). Ninety-five percent patients received a single dose of vaccine. Most of the patients had mild symptoms (63.9%), and treated at home (67.2%). Most of the patients recovered utterly (95.1%) without any death. Vaccination showed reduced disease severity (RR 0.93, 95% CI, 0.87-0.99). Conclusions: In this study it was observed that coronavirus vaccine may significantly lessen disease severity, improve clinical outcome, and prevent death among SARS-CoV-2infected patients. J Bangladesh Coll Phys Surg 2023; 41(4): 294-297